A comparative study on renewable and traditional electricity: The influence of the European Union framework and the impact of COVID-19 - Boldeanu, Florin Teodor; Clemente-Almendros, José Antonio; Seguí-Amórtegui, Luis; Duguleana, Constantin (PLoS ONE, 2023)
By means of the event study approach, we analyse the effect of COVID-19 on listed European renewable and traditional electricity companies, inside and outside the European Union, for the pandemic announcement and lockdowns. We find that the pandemic negatively affected both subsectors of electricity production, but the negative effect was more intense for renewable electricity companies, since they represent a riskier investment. Moreover, this negative effect was larger for European electricity companies than for companies from countries that do not belong to the European Union. Our results show the riskier profile of the clean energy industry together with the importance of a stable and supportive regulatory framework to develop and consolidate renewable energy. Our findings have important implications for policymakers. In addition to the intrinsic risks associated with renewable energy, this type of investment poses policy and regulatory risks, which they should take into account when evaluating future energy policies. Policymakers must be aware of the importance of these specific risks, and seek to respond to investors' expectations about long-term, stable regulations.
Keywords: renewable and traditional electricity; European Union; COVID-19; Scopus; JCR